Islamisasi di Karawang Raya Dari Syekh Qura hingga Kesultanan Islam - Arif Noor Dhaiman (Tarikh : Journal of Islamic History and Civilization, 2026)
The objective of this study is to analyze the history of Islamization in the Greater Karawang region from Sheikh Quro to the Islamic Sultanate. This study employs a qualitative research design using library research. Data credibility is tested through a five-year research period from 2021 to 2026, data triangulation, and member checking. Greater Karawang has been part of Darul Islam since the early days of the Sultanates in Cirebon and Banten. This means it was not merely a region of da’wah but also a land where Islamic Sharia was once enforced through the authority of Sultans bearing the titles Panatagama or Qaimuddin—titles signifying those who uphold religious laws. What is particularly noteworthy is that the call to jihad fi sabilillah in Cirebon and Banten—as the rulers of Karawang Raya—was closely tied to the Ottoman Caliphate, exemplified by the Ki Amuk cannon of Banten and the Macan Ali war banner, both of which bore Ottoman symbols: the Dzulfiqar sword. Karawang Raya was a land of Islamic warriors. The Rengasdengklok Incident is only a small part of the history of Greater Karawang. Subsequently, the Islamization of Greater Karawang was led by Sundanese nobles of the Aria Wangsagoparana lineage and scholars who were alumni of al-Haramain, known as the Ashab al-Jawiyyah. Among the figures involved were the Regent of Karawang, Dalem Solawat Rd. H. Muhammad Siraj Suriawinata; the Head of Karawang, Syekh Baing Rd. H. Muhammad Yusuf; and Mama Sempur Plered, Syaikh Tubagus Ahmad Bakri, along with his students in Karawang, Bekasi, Subang, and Purwakarta.